Pemanfaatan Program Manajemen Berbasis Internet (Telenursing-Telemedicine- Aplikasi Website-Smartphone) dalam Upaya Mengurangi Kekambuhan Penyakit Asma Bronchiale - Batubara, Sauqi Sahrur (Deli Medical and Health Science Journal, 2024)
Based on data from the Ministry of Health in 2020, asthma is one of the most preval___ent diseases among the Indonesian population. By the end of 2020, the number of asthma sufferers in Indonesia reached 4.5 percent of the total population, totaling more than 12 million individuals. Asthma is a chronic condition characterized by recurrent episodes and currently cannot be completely cured. However, with proper control and treatment, asthma patients can lead normal lives and have a high life expectancy. Internet-based support systems for self-management and education, along with internet and mobile technologies, are increasingly recognized as valuable tools for patients with chronic diseases. The purpose of this literature review is to identify internet-based management programs that can effectively reduce the recurrence of bronchial asthma. This literature review method employs the PRISMA flow, with database searches including Google Scholar (57 articles), ProQuest (20 articles), and Wiley (14 articles). Keywords used in the article search include internet-based disease management, bronchial asthma, and knowledge. Only 6 articles were deemed appropriate through analysis of objectives, topic suitability, research methods used, sample size, research ethics, results of each article, and encountered limitations. The findings of the literature review indicate that information systems that can be utilized and have yielded significant results in achieving positive outcomes in the management of bronchial asthma include social media features such as Twitter and WhatsApp, internet features for telecommunication or telemedicine websites, the Attend Anywhere application based on Google Chrome, Zoom, and telemedicine.